Criminal and legal protection of national security: Problems of systematization of crimes - Яремко, Галина Зіновіївна; Яремко, Г. З.; Яремко, Галина Зиновьевна; Yaremko, Halyna Z.; Yaremko, Galyna; Іванова, Наталя Сергіївна; Іванова, Н. С.; Иванова, Наталья Сергеевна; Ivanova, Natalia S.; Мандриченко, Жанна Василівна; Мандриченко, Ж. В.; Мандриченко, Жанна Васильевна; et al. (Editorial Primmate S. A. S., 2021)
The chief idea of criminal law is to protect the individual, society, and the state from criminal encroachment. Defined by the legislator in the field of protection - the basics of national security, life and health, public safety, environment, etc. are subject to comprehensive research to improve the effectiveness of criminal law protection, which is of great practical importance. The foundations of national security are a multifaceted construction that requires detailed analysis. This work is devoted to the study of the conceptual foundations of systematization of crimes against the foundations of national security of Ukraine as one of the fundamental aspects of the theoretical basis of the criminal law system. The work aims to study the conceptual foundations of the systematization of crimes against the foundations of national security of Ukraine. The subject of study: problematic aspects of systematization of crimes against the foundations of national security of Ukraine. The object of research: approaches to the systematization of crimes against the foundations of national security of Ukraine. The authors used the following methods: observation, generalization, analysis, synthesis, experiment, formalization. As a result of the study, the universal definition of national security, the feasibility of a system of crimes against the foundations of national security of Ukraine, determined as an experiment to develop subgroups under Section I of the Special Part of the Criminal Code.

Основне призначення кримінального права – захист особи, суспільства та держави від злочинних посягань. Визначені законодавцем сфери охорони –основ національної безпеки, життя і здоров’я особи, громадської безпека, довкілля та ін. підлягають всебічному дослідженню задля удосконалення ефективності кримінально-правового захисту, що має велике практичне значення. Основи національної безпеки є багатоаспектною конструкцією, що потребує детального аналізу. Дана робота присвячена саме дослідженню концептуальних основ систематизації злочинів проти основ національної безпеки України як одного з основоположних аспектів теоретичного підґрунтя системи кримінального права. Метою роботи є дослідження концептуальних основ систематизації злочинів проти основ національної безпеки України. Предмет дослідження: проблемні аспекти систематизації злочинів проти основ національної безпеки України. Об’єкт дослідження: підходи до систематизації злочинів проти основ національної безпеки України. Дослідження проведено за допомогою таких методів: спостереження, узагальнення, аналізу, синтезу, експерименту, формалізації. У результаті проведеного дослідження було визначено універсальне визначення національної безпеки, доцільність системи злочинів проти основ національної безпеки України, запропоновано в якості експерименту розробити підгрупи у рамках Розділу І Особливої частини ККУ.
Yaremko G. Criminal and legal protection of national security: Problems of systematization of crimes / G. Yaremko, N. Іvanova, Z. Mandrychenko, O. Gorpyniuk // Amazonia Investiga. – Vol. 10. - Issue 47. – Editorial Primmate S. A. S., 2021. – P. 207-215.
Keywords: bases of national security; national security of Ukraine; system of crimes against national security; crime; основи національної безпеки; національна безпека України; система злочинів проти національної безпеки; злочин; Research Subject Categories::LAW/JURISPRUDENCE